Ecocide Under Occupation and Conflict: The Cases of Palestine and Sudan - Venkatachalapathy,Shravan; Simic,Szebasztián (2025)
This thesis investigates ecocide as a form of environmental violence by state and non-state actors, reframing ecological destruction as a political and antagonistic act rather than an accidental byproduct of development. This research emphasises the active participation of state institutions in facilitating and perpetuating large-scale environmental harm while deterring efforts to legally frame ecocide as an international crime. Thereby, accentuating the need to enhance preparedness among vulnerable communities such as Palestine and Sudan through international partnerships and aid. Using a critical qualitative methodology, data were collected through semi-structured interviews, case studies, and literature review. The data was analysed through a combination of First Cycle Coding methods—Attribute, Descriptive, In Vivo, and Simultaneous Coding—followed by Pattern Coding in the Second Cycle. This approach prioritised participant perspectives and preserved the integrity of information prior to thematic development. Findings reveal that ecocide is deeply intertwined with histories of neocolonialism, the cataclysmic effects of the genocide-ecocide nexus, and systemic political and legal neglect. Participants frequently expressed ecocide in terms of cultural erasure, environmental harm, detrimental effect on human life and community disempowerment. The study concludes that ecocide must be understood as a form of state-sanctioned violence with political, social, and legal implications. It calls for the inclusion of ecocide in international legal frameworks and highlights the importance of bolstering the capacities of vulnerable regions through the core principles of preparedness, funding, and prioritisation of local community needs.
Keywords: Ecocide; preparedness; monitoring; capacity; colonialism; international law; humanitarian aid